Graphene-based nanostructures: Plasmonics in the THz range - Bludov, Yuliy V. (2015)
The properties of surface plasmon-polaritons (SPPs) in graphene are discussed and several possible ways of coupling electromagnetic radiation in the terahertz (THz) spectral range to this type of surface waves are described: (i) the attenuated total reflection (ATR) method employing a prism, (ii) graphene-based gratings or graphene monolayers with modulated conductivity, (iii) a metal stripe on top of the graphene layer, and (iv) a nanoparticle located above it. Potentially interesting for applications SPP effects, such as switching, modulation and polarization of THz radiation, as well as its enhanced absorption in graphene, are considered. The discussion also concerns the impact of the nonlinear properties of graphene, such as optical bistability.